Identifikasi Dampak Kebisingan Penambangan di Kecamatan Bahodopi, Kabupaten Morowali, Sulawesi Tengah - Siharis, Al Amin; Amin, Fitrani; Abriansyah; Aldiyansyah; Shaddad, Aqsal Rhamadan (FAKULTAS TEKNIK UMKENDARI, 2024)
PT. Cahaya Ganda Gindi is a nickel company engaged in lateritic nickel mining. The company's nickel ore mining activities have now entered the operational phase, including topsoil stripping, overburden removal, lateritic nickel mining, and lateritic nickel transportation. The mining area, which is located close to residential settlements, has some impact on community activities. Therefore, these impacts need to be managed to prevent disturbances to the daily activities of local residents. The production activities, which involve overburden stripping and lateritic nickel ore extraction using heavy machinery, inevitably generate high levels of noise that may affect the hearing of nearby residents. Noise level testing is conducted in the mining area, jetty, and residential areas by measuring noise levels at specific points. The collected data is then analyzed to determine whether the noise levels remain within the permissible limits. The goal is to ensure that the noise does not exceed the established threshold, allowing the community to carry out their activities normally.